Analysis of Factors Affecting Employee Performance at PT. Pertamina Trans Kontinental Marine Regional I Sungai Pakning - Hijeriah, E.Maznah; Erlianti , Dila (Program Studi Ilmu Administrasi Negara FISIP UMRAH, 2025)
Every organization or company requires resources to achieve its objectives. Human resources are the most determining factor in every company, so it can be said that human resources are one of the main assets in a company to achieve corporate goals. PT. Pertamina Trans Kontinental focuses on offshore activities that assist offshore oil and gas exploration for lessees of ships owned by the company and third-party vessels. In carrying out its duties and functions, PT Pertamina Trans Kontinental Marine Regional I Sungai Pakning is supported by human resources with the status of Organic Employees and Non-Organic Employees totaling 48 people. This company also runs business activities in the shipping and maritime service industry sector and realizes that customer service is the top priority, so the organization continues to strive to make its services more effective and efficient. In measuring the Factors that Influence Employee Performance at PT. Pertamina Trans Kontinental Marine Regional I Sungai Pakning from 48 respondents with 5 (five) indicators, namely Barriers, Performance Expectations, Consequences, Feedback, and Individual Knowledge, Skills and Abilities. The data analysis used Descriptive Statistics. With the Likert scale, scores for each assessment were obtained with a score range of 1-5. Respondent answers varied with criteria: Strongly Agree, Agree, Neutral, Disagree, and Strongly Disagree. Based on the recapitulation of respondent responses for all indicators on the Factors that Influence Employee Performance at PT. Pertamina Trans Kontinental Marine Regional I Sungai Pakning, the research results can be categorized as Strongly Agree.